Nursing Burnout to Infection Prevention and Control Measures Inpatient - Widyani, Yeni; Hutahaean, Serri (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Health is very important for a person’s life to be able to carry out daily activities comfortably. Hospitals as health service providers for the community play an important role in maximizing the level of health of a community, but conditions in the field show that not a few people who seek treatment at hospitals have the opportunity to get new diseases that have not been suffered before or HAIs (Healthcare Associated Infections). The purpose of this study was to determine the relationship between nurse burnout to infection prevention and control measures inpatient room of X Kuningan Hospital. This research used a descriptive-analytic research method with a cross-sectional approach. Total sampling was 75 subjects. The results of the chi-square test obtained a p-value <0,05 (0,002), which means that there was a relationship between nurse burnout and infection prevention and control measures. The recommendation from this study is that hospital managers need to improve the quality of nurses by supervising and preventing burnout on nurses to take proper infection prevention and control (PPI) measures.